Between Exclusivity and Inclusivity of Institutions: Examining the Role of the Indonesian Ulema Council and Its Political Fatwa in Handling the Spread of Covid-19 - Muhammad Lutfi Hakim; Zaenuddin Hudi Prasojo; Muhammed Sahrin bin Haji Masri; Muhammad Fauzinudin Faiz; Fuad Mustafid; Busro Busro (Khazanah Hukum, 2023)
The Indonesian Ulema Council (Majelis Ulama Indonesia, MUI) was stigmatised as an institution accommodating conservative Islamic groups’ interests post-New Order. However, the religious fatwas produced by the MUI during the Covid-19 pandemic in 2020 had prioritised independence so that it returned to its original role, namely as a translator of government policies. For this reason, this article aims to examine the MUI fatwas and its relationship to state policies in tackling the spread of Covid-19. It is a qualitative research study with a historical approach, examining the content of seven fatwas issued by the Fatwa Commission (Komisi Fatwa) between March and July 2020 as the primary data sources. This study found that MUI’s legal arguments and methods are more inclusive, flexible, and progressive towards socio-religious problems. These fatwas have become a reference for the government in taking policies to suppress the spread of Covid-19. It is reinforced by the fact that several fatwas issued by MUI were used as guidelines by the government in formulating policies to curb the spread of Covid-19. Therefore, the authors argue that the MUI’s fatwa politics not only serve the interests of the Muslim community but also align with the state’s interests in tackling the spread of Covid-19. Thus, the debate regarding the stigmatisation of the role of MUI can be dismissed through these findings, providing new insights into the dynamic interplay between religious and legal frameworks.